2013
DOI: 10.1590/s2176-94512013000300017
|View full text |Cite
|
Sign up to set email alerts
|

Superficial morphology and mechanical properties of in vivo aged orthodontic ligatures

Abstract: The elastic ligatures aged in the oral environment showed higher superficial degradation and lower loss of mechanical properties after the maximum experimental period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
0
8
0
6
Order By: Relevance
“…Guimarães et al (2013) revealed that aging procedures for four weeks in the oral environment led to a decrease in the ultimate strength in accordance with an increase in surface roughness. They stated that the use in the oral environment led to a 50% reduction on the initial force in the first 24 hours (in vitro study) and a 74% reduction on initial force after the same degradation time.…”
Section: Discussionmentioning
confidence: 85%
“…Guimarães et al (2013) revealed that aging procedures for four weeks in the oral environment led to a decrease in the ultimate strength in accordance with an increase in surface roughness. They stated that the use in the oral environment led to a 50% reduction on the initial force in the first 24 hours (in vitro study) and a 74% reduction on initial force after the same degradation time.…”
Section: Discussionmentioning
confidence: 85%
“…On the contrary, the OPG concentration on the conventional preadjusted bracket group started to increase approaching its baseline value at 168 hours, which indicates less bone resorption than the self-ligating bracket group at that specific time period. This could have happened due to aging of the elastic ligatures as stated by Guimarães et al 21 The orthodontic elastomers, which were used on our conventional bracket group, were biodegraded in the oral environment by hydrolyses, which leads to relaxation of the elastomers. The consequence of the relaxation phenomenon is a decrease on the mechanical energy transmitted to the tooth resulting in reduction of tooth movement effectiveness.…”
Section: Discussionmentioning
confidence: 92%
“…Dessa forma, foi realizado o teste de tração elástica na Máquina de Ensaio Mecânico Universal (EMIC DL 2000, São José dos Pinhais, PR, Brasil). Os protocolos utilizados seguiram metodologia de outros trabalhos já publicados no que diz respeito ao uso de ganchos indeformáveis de aço inoxidável para prender as ligaduras e à velocidade de distensão de 5mm/min (Souza et al, 2008;Guimarães et al, 2013;Ahrari et al, 2016).…”
Section: Leitura Final-pasta Convenc-t1 Pacientes Força Max (Kgf) Forunclassified
“…Por fim, para detectar visualmente e qualitativamente o aspecto das ligaduras submetidas a pasta clareadora e convencional, entendeu-se que a observação pela Microscopia Eletrônica de Varredura seria válida, na tentativa de relacionar a presença de trincas, rachaduras, algum tipo de desgaste, porosidade ou deformação a maior ou menor grau de pigmentação dependendo do dentifrício utilizado (Guimarães, et al, 2013e Fernandes et al, 2014.…”
Section: Leitura Final-pasta Convenc-t1 Pacientes Força Max (Kgf) Forunclassified
See 1 more Smart Citation